2001
DOI: 10.1073/pnas.171321298
|View full text |Cite
|
Sign up to set email alerts
|

AML1-ETO expression is directly involved in the development of acute myeloid leukemia in the presence of additional mutations

Abstract: The t(8;21) is one of the most frequent chromosomal abnormalities associated with acute myeloid leukemia (AML). The translocation, which involves the AML1 gene on chromosome 21 and the ETO gene on chromosome 8, generates an AML1-ETO fusion transcription factor. To examine the effect of the AML1-ETO fusion protein on leukemogenesis, we made transgenic mice in which expression of AML1-ETO is under the control of the human MRP8 promoter (hMRP8-AML1-ETO). AML1-ETO is specifically expressed in myeloid cells, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
280
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 383 publications
(308 citation statements)
references
References 52 publications
27
280
0
1
Order By: Relevance
“…It may be a common underlying mechanism for the pathogenesis in AML1-associated leukemia. However, recently generated transgenic or knock-in mice showed that AML1 mutations are critical for the development of AML, but that one or more additional mutations are necessary for leukemogenesis [10][11][12]. This accepted hypothesis is supported by the cytogenetic findings in the case of our patient exhibiting a complex karyotype.…”
supporting
confidence: 70%
“…It may be a common underlying mechanism for the pathogenesis in AML1-associated leukemia. However, recently generated transgenic or knock-in mice showed that AML1 mutations are critical for the development of AML, but that one or more additional mutations are necessary for leukemogenesis [10][11][12]. This accepted hypothesis is supported by the cytogenetic findings in the case of our patient exhibiting a complex karyotype.…”
supporting
confidence: 70%
“…, 2004). RUNX1-ETO expression in conjunction with treatment with the mutagen N-ethyl-N-nitrosourea (ENU) resulted in myeloid leukemia or granulocytic sarcoma (Yuan et al, 2001;Higuchi et al, 2002). Therefore, RUNX1-ETO is able to predispose myeloid precursors to transformation.…”
Section: Discussionmentioning
confidence: 99%
“…3 The creation of AML1-ETO is necessary, but not sufficient, for leukemogenesis in AML with t(8;21). 4 The recently developed WHO classification of hematologic malignancies recognizes AML with t(8;21) as a distinct clinicopathologic entity. 5 This form of AML is found more frequently in children and young adults 6 and patients are predisposed to extramedullary localization.…”
mentioning
confidence: 99%